RELATIONSHIP BETWEEN TEACHER MOTIVATION IN GUIDING STUDENT LEARNING DIFFICULTIES AND LEARNING ACHIEVEMENT - Paris, Zul; Utaya, Sugeng; Setyosari, Punaji; Sin, Ishak (Journal of K6, Education and Management, 2018)
This study aims to find how is the level of teacher motivation in guiding student learning difficulty and learning achievement of elementary school students in technical implementation unit area of Kuripan Subdistrict, Barito Kuala District. It is a correlation to find the relationship between independent and dependent variable in students. Learning difficulty is a condition in learning process where students cannot learn as they should be. Learning difficulty is basically those that appear in various behaviors whether directly or indirectly.